2015
DOI: 10.1007/s11032-015-0331-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of hybrid breakdown in an indica/japonica cross and fine mapping of a quantitative trait locus qSF-12 in rice (Oryza sativa L.)

Abstract: Hybrid breakdown is an important form of post-zygotic reproductive barriers, often arising from hybrid progeny between two varietal groups of Asian cultivated rice (Oryza sativa L.), indica and japonica. However, the genetic mechanism underlying the hybrid breakdown remains unclear. In the present study, a chromosomal segment substitute line (CSSL) population together with a backcross inbred line population, derived from the same cross of Sasanishiki/Habataki, were employed for genetic analysis of rice hybrid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…He suggested that hybrid breakdown occurs as adaptive gene complexes that had evolved in each of the parents are broken up during meiosis. Hybrid breakdown has been reported after self‐pollination or intercrossing of interspecific hybrids in other crops, as well (Li et al, 1997, 2015; Johansen‐Morris and Latta, 2006; Ellison and Burton, 2008; Matsubara et al, 2015; Dai et al, 2016).…”
Section: Barriers To the Use Of Wild Relativesmentioning
confidence: 99%
“…He suggested that hybrid breakdown occurs as adaptive gene complexes that had evolved in each of the parents are broken up during meiosis. Hybrid breakdown has been reported after self‐pollination or intercrossing of interspecific hybrids in other crops, as well (Li et al, 1997, 2015; Johansen‐Morris and Latta, 2006; Ellison and Burton, 2008; Matsubara et al, 2015; Dai et al, 2016).…”
Section: Barriers To the Use Of Wild Relativesmentioning
confidence: 99%
“…F 2 hybrid sterility is observed in various plant species ( Kubo and Yoshimura, 2005 ; Sweigart et al, 2006 ; Yi et al, 2006 ; Li et al, 2015 ). Unlike F 1 sterility, gamete abortion can be observed in some F 2 individuals derived from a completely fertile F 1 hybrid.…”
Section: Complicated Genetic-interaction-network Involve In Hybrid Smentioning
confidence: 99%
“…The genetics of HB have been studied in rice, especially in interspecific ( Oryza. sativa × O. glumaepatula and O. sativa × O. nivara ) and intersubspecific ( japonica and indica ) hybridizations ( Fukuoka et al 1998 , 2005 , Ichitani et al 2012 , Jiang et al 2008 , Kubo and Yoshimura 2002 , 2005 , Li et al 1997 , 2015 , Matsubara et al 2006 , 2007 , 2015 , Miura et al 2008 , Oka 1957 , 1978 , Oka and Doida 1962 , Okuno 1986 , Sato and Morishima 1988 , Sobrizal et al 2001 , Wu et al 1995 , Yamamoto et al 2007 , 2010a , Yokoo 1984 ). A simple genetic mechanism based on complementary recessive genes has been proposed.…”
Section: Introductionmentioning
confidence: 99%